Effects of brand placement and player involvement on brand awareness: an empirical study on online game players - Bonit Bogonondo; Yessy Artanti (Diponegoro International Journal of Business, 2019)
This paper examines the effects of brand placement and player involvement on brand awareness. The data in this study were collected from questionnaires distributed to 150 game players of online game with snowball sampling. Data analysis used multiple regression  analysis. However, our prediction that there were effect of brand placement and player involvement on brand awareness was not supported. We presents the discussions in this paper.